Comparative Survival Analysis of Anti‐Angiogenic Agent Plus Immunochemotherapy in NSCLC Patients After Frontline EGFR‐TKI Treatment: A Retrospective Cohort Study - Yi‐Tse Su; Shu‐Farn Tey; Chung‐Ta Lee; Chien‐Yu Lin; Jeng‐Shiuan Tsai; Chien‐Chung Lin; Chin‐Wei Kuo (Kaohsiung Journal of Medical Sciences, 2025)
ABSTRACT Advanced‐stage EGFR‐mutated lung non‐small cell lung cancer (NSCLC) challenges current treatment paradigms, particularly after frontline EGFR‐TKI therapy failure. This study investigates the survival impact of combined anti‐angiogenic agent and immunochemotherapy (AICT) for this population. We retrospectively analyzed NSCLC patients at National Cheng Kung University Hospital from January 2010 to December 2022, focusing on those who had disease progression beyond frontline EGFR‐TKI treatments. Survival outcomes were assessed through progression‐free survival (PFS) and overall survival post‐TKI failure (OSpTKI). Propensity score was employed to match patients, with Kaplan–Meier curve and multivariable Cox regression analysis determining the survival benefits. Analyses were also performed for subgroups based on PD‐L1 level, treatment lines, and regimens. A total of 412 patients were enrolled, with 27 receiving AICT. Compared to patients who did not receive AICT, those who received AICT had longer PFS (5.9 vs. 3.9 months, p = 0.024) and longer OSpTKI (17.9 vs. 11.9 months, p = 0.018). The observed survival advantage in PFS and OSpTKI was consistent in both the original cohort (for PFS: hazard ratio [HR] = 0.59, 95% confidence interval [CI] = 0.39–0.90, p = 0.014; for OSpTKI: HR = 0.41, 95% CI = 0.24–0.69, p < 0.001) and after propensity score matching (for PFS: HR = 0.56, 95% CI = 0.35–0.98, p = 0.014; for OSpTKI: HR = 0.45, 95% CI = 0.26–0.79, p = 0.006). In the subgroup analyses, patients with PD‐L1 ≥ 1%, those who received AICT as a second‐line therapy, or those treated in conjunction with pemetrexed showed a PFS benefit. AICT improves survival outcomes in advanced‐stage EGFR‐mutated NSCLC, advocating for its integration into treatment regimens.